Radial artery pseudoaneurysm successfully treated by compression bandage. Issue 2 (1st February 2003) - Cozzi, D A; Morini, F; Casati, A; Pacilli, M; Salvini, V; Cozzi, F
Abstract : In children, surgery for radial artery pseudoaneurysm (PA) may be followed by growth retardation of the hand because of inadequate blood flow. We believe this is the first report of a child with PA of the radial artery cured by compression bandage. Conservative management is a safe and valuable initial treatment option for uncomplicated radial PA.